Visible Light Channel Modeling for High-data Transmission in the Oil and Gas Industry - Ibhaze, Augustus; Orukpe, Patience; Edeko, Frederick (Journal of Science and Technology, 2020)
High-speed communication has been a major concern in the oil and gas field for downhole data acquisition, transmission and exploration. This has necessitated this investigation of the promising license-free broadband visible light spectrum for improved communication reliability in the oil and gas field. A visible light communication (VLC) multiple input multiple output (MIMO) communication link is proposed as the drill pipe wireless communication link. The proposed model was seen to perform more optimally using the maximum likelihood detection technique in comparison with zero forcing at reduced bit error rates and improved throughput relative to increasing values of the signal to noise ratio (SNR). Although this investigation proposes a novel design of the wireless drill pipe, its adoption will greatly reduce exploration time thereby increasing the return on investment as data transmission speed increases.